ANALISIS RISIKO ERGONOMI PADA PEKERJA OFFICE BOY DI PT. XYZ (STUDI KASUS PENDISTRIBUSIAN AIR GALON) - Tri Novita Sari; Asri Amalia Muti; Nofan Hadi Ahmad (Universitas Putera Batam, 2022)
An Office Boy (OB) has a big role in helping employees in a company. PT XYZ is one of modern office building located in Jakarta’s prime business district along Jalan Thamrin, Jakarta. PT XYZ has office boys, the office boy’s job includes cleaning and tidying the room and office equipment, serving requests of employees and company guests. The job of distributing gallons of water carried out by the office boy from the pantry to the 13 divisions is a tough job. It is important to know the risk and the force that occurs on the spine as well as an ergonomic risk analysis. The force received by the spine (L5/S1) is 2253.34 N, where the force is still within normal limits, but based on the REBA method the activity of lifting gallons of water poses a very high ergonomic risk. This risk can cause injury, especially if it is done for a long period of time. It is necessary to improve work posture such as lifting a lower body posture/squatting or with another device.